Agricultural use and pH correction of anaerobic sewage sludge with acid pH. (1st December 2020) - Pereira, Ivan dos Santos; Bamberg, Adilson Luís; Oliveira de Sousa, Rogério; Monteiro, Alex Becker; Martinazzo, Rosane; Posser Silveira, Carlos Augusto; de Oliveira Silveira, Andressa
Abstract: Agricultural use is the main way of recycling sewage sludge. Besides providing nutrients and organic matter to crops and soils, it is an important alternative for recycling this residue. However, problems during the sewage treatment process may generate sludge batches with an acidic pH. Thus, it is essential to understand the consequences of using such sludge on soils and plants, and to explore ways to overcome this limitation. The objective of this study was to evaluate addition rates of anaerobic sewage sludge (ASS) with acidic compositions on the soil fertility and performance of lettuce plants. Additionally, a methodology for pH correction of ASS with acidic pH is proposed. An agronomic experiment was conducted in a greenhouse using seven addition rates of ASS (0.0, 0.25, 0.5, 1, 2, 4 and 8 g kg −1 in dry basis), treated with an additional step of disinfection (solarization), and applied in an Albaqualf soil cultivated with lettuce ( Lactuca sativa ). Soil and leaf chemical composition, as well as chlorophyll index and the dry matter of lettuce leaves were evaluated. Failures during the acidogenesis phase of the anaerobic digestion process were probably the cause of ASS acidification. Although this ASS increased soil fertility indicators and plant dry matter, it significantly reduced soil pH, thereby requiring a complementary assay to correct its pH up to 6.0, which was achieved through liming. Anaerobic sewage sludges with an acidic pH can be effectively used in agriculture after being dried and disinfected through solarization, followed by pH correction, avoiding negative impacts on soil chemical attributes and plant response. Graphical abstract: Image 1 Highlights: Anaerobic sewage sludge with acid pH were evaluated for agricultural purposes. Acid pH limit the benefits of sewage sludge on soil fertility and crop response. A simple and fast method of pH correction through limestone addition was proposed. Long stay solarization provided suitable levels of pathogens for agricultural use. Solarization and pH correction improved agronomic aspects of anaerobic sewage sludge.